The Psychological Issues of Bonded Labour in Fuel Smuggling as Modern form of Slavery in Makran Division of Baluchistan - Nosheen Murad; Prof. Dr. Muhammad Usman Tobawal; Dr. Muhammad Makki Kakar (Review Journal of Social Psychology & Social Works, 2025)
Debt bondage, or bonded labor, is increasingly recognized as modern form of slavery, particularly in fuel smuggling. In the context of fuel smuggling, individuals find themselves coerced into servitude due to debts incurred through illegal means, such as exploitation by smugglers and recruiters. The study discovers psychological issues faced by victims of bonded labor within the fuel smuggling trade in the Makran division of Balochistan, Pakistan. This qualitative study emphases on 14 participants who are involved in fuel smuggling-related bonded labor. Using in-depth interviews as the study approach, data was collected through snowball sampling, which allowed the identification of persons enslaved in the cycle of debt bondage. The findings suggest that the fuel smuggling sector, like other forms of bonded labor, causes extreme psychological distress to individuals involved. They are caught up in a vicious cycle of debt repayment under dangerous and exploitative conditions and situations that they feel, they are always anxious, depressed, stressed and traumatized. Their work comes with its own risks, but the additional social and legal dangers associated with fuel smuggling or its consequences exacerbate the psychological problem. The research calls to address bonded labor in fuel smuggling, by implementing not only the legal framework to end the illegal fuel trade but mental health to safeguard the victims. Along with the poverty alleviation from debt bondage, there is a greater need for societal, institutional and psychological support systems in the fight and eradication of debt bondage.